Electron elastic scattering off a Tensor-polarized Deuterium Internal Target - Vodinas, N.; Alarcon, R.; Anghinolfi, M.; Arenhövel, H.; van Bommel, R.; Botto, T.; Bouwhuis, M.; van den Brand, J.F J.; Bucholz, M.; Bulten, H. J.; Choi, S.; Comfort, J.; et al. (HNPS Advances in Nuclear Physics, 2019)
The tensor analyzing power Γ20 in elastic electron-deuteron scattering has been measured in the four momentum transfer region between 1.4 and 3.2 fm l using the Internal Target Facility at NIKHEF. Tensor-polarized deuterium is produced in an Atomic Beam Source and injected into a storage cell. Scattered electrons and recoil deuterons were detected in coincidence with two large acceptance nonmagnetic detectors.